Faktor-Faktor Yang Berhubungan dengan Penyembuhan Luka Post Sectio Caesarea di RS Efarina Kota Berastagi - Yesica Geovany Sianipar; Agustina Br Padang; Magdalena Br Barus; Hariati Br Purba; Sodiria Zega; Esra E Sinaga (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Maternal mortality in Indonesia is still dominated by three main causes of death:bleeding, hypertension in pregnancy, and infection. One high MMR may be due to complications in labor, including SC. Complications that can occur after caesarean section surgery are infections, called postoperative morbidities. The purpose of this study to determine the Factors Associated With Healing Post SC Injury At Efarina Berastagi Hospital. This research type is analytic survey research with cross sectional. The data used is using chis-quare test. The population are 36 peoples and the total sample of 36 peoples. From result of research indicate that from result of Chi-square statistic test at 95% confidence level with α = 0,05, obtained by Asymp. Sig age (0. 001), nutrition (0.041), and early mobilization (0.035) <α (0.05). The conclusion of the study is the relationship of age, nutrition and early mobilization with SC with Post Injury Healing at Efarina Berastagi Hospital in 2023. It is suggested to the hospital to further improve the quality of health service and the managerial of the house more emphasize the implementation of early mobilization for SC mother to avoid infection and to accelerate the recovery of cesarean section injection, and to nurses and midwives to provide and monitoring of the implementation of early mobilization more intensively and to observe nutritional status of post SC mother to accelerate wound healing.